Anti-GPIIb/IIIa Drugs: Current Strategies and Future Directions - Coller, Barry S. (Thrombosis and Haemostasis, 2001)
Three platelet glycoprotein (GP) IIb/IIIa receptor antagonists have been approved as adjunctive therapy to decrease the ischemic complications of percutaneous coronary interventions (PCI) and/or unstable angina. They include the chimeric murine/human monoclonal antibody 7E3 Fab fragment (abciximab), a cyclic heptapeptide based on the KGD amino acid sequence (eptifibatide), and a nonpeptide mimetic of the RGD sequence (tirofiban). The agents are very effective in providing both short-term and long-term benefit after PCI, and one agent has also demonstrated a progressive long-term mortality benefit. The long-term mortality benefit is highly cost-effective when compared to other medical interventions. The benefits in treating unstable angina without PCI are less dramatic and robust, with some agents providing no benefit. Severe thrombocytopenia is an infrequent, but potentially serious, complication of therapy with all of the agents. The risk of major bleeding is increased only minimally or not at all by the drugs. Currently, a number of new indications for GPIIb/IIIa antagonists are under study, including acute myocardial infarction (± thrombolytic therapy, ± PCI) and stroke. In addition to their impact on improving outcome, the results of clinical trials with these agents provide crucial insights into the contribution of GPIIb/IIIa-mediated platelet function in the pathophysiology of thrombotic vascular disease.
Keywords: Abciximab; tirofiban; eptifibatide; angioplasty; unstable angina; antithrombotic therapy